2011
DOI: 10.1111/j.1755-148x.2011.00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional defects of peripheral regulatory T lymphocytes in patients with progressive vitiligo

Abstract: Summary Auto‐reactive cytotoxic T lymphocytes play a key role in the progressive loss or destruction of melanocytes in vitiligo but the mechanism underlying the loss of self‐tolerance is unknown. A deregulation of regulatory T‐cell biology has recently been suggested. The analysis of the suppressive effects of peripheral T regulatory cells in vitiligo patients revealed a functional defect in seven of 15 cases. This defect was strongly correlated with disease activity. The evaluation of the percentage of periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
89
3
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(115 citation statements)
references
References 64 publications
14
89
3
9
Order By: Relevance
“…More recently, repigmentation in a mouse model of spontaneous epidermal depigmentation was found to be accompanied by an increased Treg cell infiltration, suggesting their importance in preventing an ongoing immune response against melanocytes [17]. To date, several studies have indicated perturbations in Treg cell numbers and/or function in vitiligo patients [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Such alterations might lead to the higher levels and activation of cytotoxic T cells (Fig.…”
Section: Regulatory T Cells In Vitiligomentioning
confidence: 99%
See 4 more Smart Citations
“…More recently, repigmentation in a mouse model of spontaneous epidermal depigmentation was found to be accompanied by an increased Treg cell infiltration, suggesting their importance in preventing an ongoing immune response against melanocytes [17]. To date, several studies have indicated perturbations in Treg cell numbers and/or function in vitiligo patients [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Such alterations might lead to the higher levels and activation of cytotoxic T cells (Fig.…”
Section: Regulatory T Cells In Vitiligomentioning
confidence: 99%
“…Several studies have been carried out to look for alterations in Treg cell numbers in vitiligo (Table 1) [10][11][12][13][14][15][16][17][18][19][20][21][22][23]26,27]. Assessment of circulating Tregs by flow cytometric analysis has revealed a decrease in their numbers in vitiligo patients compared to controls [10,11,13].…”
Section: Regulatory T Cell Numbersmentioning
confidence: 99%
See 3 more Smart Citations